1991
DOI: 10.1021/ma00013a027
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric property-electrooptical effect relationships of polymer/liquid-crystal composite films

Abstract: The dielectric properties of a polymer/liquid-crystal (LC) composite film and their influence on the electrooptical response have been investigated. The composite film in which an LC material is embedded as a continuous phase in a three-dimensional spongy polymer matrix shows an electrooptical effect based on a novel concept of light scattering. The electrooptical response speed for the composite film is proportional to ~AeE3, where Ac is the dielectric anisotropy of the LC, and E is the electric field. The di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 4 publications
3
56
0
Order By: Relevance
“…26, No. 8,1994 of them are same. If the light scattering of the composite film upon an electric field -OFF state only depends on the mismatch between nv and refractive index of LC, the lower transmittance (0%) of the composite film (C) than that (7%) of the composite film (B) means that the composite film (C) has the much more light scattering points between matrix polymer and LC than those of the composite film (B), because their components, polymer and LC are same.…”
Section: Component Ratio Dependence Of the Aggregation Structure And mentioning
confidence: 99%
See 2 more Smart Citations
“…26, No. 8,1994 of them are same. If the light scattering of the composite film upon an electric field -OFF state only depends on the mismatch between nv and refractive index of LC, the lower transmittance (0%) of the composite film (C) than that (7%) of the composite film (B) means that the composite film (C) has the much more light scattering points between matrix polymer and LC than those of the composite film (B), because their components, polymer and LC are same.…”
Section: Component Ratio Dependence Of the Aggregation Structure And mentioning
confidence: 99%
“…26, No. 8,1994 properties of the composite films shown in Figure 8 upon electric field -ON and -OFF states. The composite film (C-1) and (C) showed same transmittance (almost 1 %) upon an electric field -OFF state.…”
Section: Construction Of the Composite Film With High Transparent-ligmentioning
confidence: 99%
See 1 more Smart Citation
“…Blends of low molecular-weight liquid crystals (LC) with polymers have been extensively studied (1)(2)(3)(4)(5), because such mixtures are expected to be useful as materials for electro-optical applications. Many studies have been reported on the phase behavior of blends of LC with flexible-chain polymers, such as poly(ethylene oxide) (3)(4)(5), polystyrene (3)(4)(5), and poly(methyl methacrylate) ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 -i 9 The light scattering state is dependent on optical heterogeneties in the composite film, such as a spatial distortion of nematic directors and/or mismatching in refractive indices of the components. 15 Consequently, the light scattering and light transmission switching properties of the composite film are decisively influenced by the phase separated structure in the composite film. It is, therefore, necessary to study the phase separation mechanism during the solvent evaporation to control the phase-separated structure of the composite film.…”
mentioning
confidence: 99%